Geochemical analyses of Jewish chalk vessel remains from Roman‐era production and settlement sites in the southern Levant. (5th August 2020) - Adler, Y.; Ayalon, A.; Bar‐Matthews, M.; Flesher, R.; Yasur, G.; Zilberman, T.
Abstract : Vessels made of chalk are common at Jewish sites throughout the southern Levant during the Roman period, apparently because stone was perceived to be impervious to ritual impurity. The study analyses samples from settlement and production sites to determine whether distinctive geochemical compositions might relate to specific source locations, and thus to provide the basis for conducting future large‐scale provenance studies. Distinctions between major elements, trace and rare‐earth elements as well as δ 18 O and δ 13 C isotopic compositions make it possible to discriminate between chalk sourced from Galilee and chalk from Judea.